The Effect of Hedonic Value and Utilitarian Value on Buying Interest with Consumer Attitudes as Mediation - Nida Al Hafiyya Nida; Sumadi (Jurnal Economic Resource, 2023)
This study aims to examine the influence of hedonic values and utilitarian values on consumer attitudes and purchase intentions. This study also examines the effect of consumer attitudes on purchase intention. This study conducted a survey of consumers at a coffee shop in Purwokerto. A pilot test was conducted on 30 initial respondents to test the validity and reliability of the instrument. Respondents who participated in this study were 200 Coffee Shop consumers in Purwokerto. Hypothesis testing using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the analysis conclude that hedonic values and utilitarian values are statistically proven to have a positive and significant influence on attitudes and purchase intentions; Besides that, this study also proves that attitude has a positive and significant influence on purchase intention